Mammal use of riparian corridors in semi‐arid Sonora, Mexico. Issue 1 (18th October 2022) - Ragan, Kinley; Schipper, Jan; Bateman, Heather L.; Hall, Sharon J.
Abstract: Wildlife populations in semi‐arid regions are increasingly challenged by human activities and dependent on the connectivity of riparian corridors for access to surface water. The Madrean Archipelago is a biodiversity hotspot along the arid United States–Mexico borderlands that support both Neotropical and Nearctic wildlife. Infrastructure development (e.g., the border wall and the expansion of Mexican Federal Highway 2) in this region inhibits wildlife movement along the transnational mountain archipelago by disconnecting habitat. To explore the relationship between habitat variables and mammal use of riparian corridors in northern Sonora, Mexico, we collected data from 19 motion‐sensitive cameras between October 2018 and April 2019 and used single‐season occupancy models and Royle‐Nichols abundance estimation models to analyze our data. We recorded 21 species of mammals, including the first sighting of jaguar ( Panthera onca ) in this region in 25 years. River characteristics (distance from river, riparian corridor width, water availability), remoteness (distance from highway, productivity, elevation), and topographic variety (vertical elevation difference) influenced patterns of occupancy probability and estimated abundance of mammals >1 kg, but the strength and direction of these relationships varied by species. Additionally, intermittently wet desert washes were comparable in species richness to the perennial system. These results highlight the importance of examining physical and biological aspects of habitat. This is especially true when identifying corridors where mitigation structures should be placed to improve wildlife connectivity in biodiversity hotspots like the Madrean Archipelago and semi‐arid ecosystems worldwide. Abstract : Wildlife populations in semi‐arid regions are increasingly challenged by human activities and dependent on the connectivity of riparian corridors for water. Our data show that river characteristics (distance from river, riparian corridor width, water availability), remoteness (distance from highway, productivity, and elevation), and topographic variety (vertical elevation difference) informed patterns of both occupancy probability and relative habitat use of mammals >1 kg, but the strength and direction of these relationships varied by species. These results highlight the importance of examining both physical and biological aspects of habitat variability.